2021
DOI: 10.3390/educsci11100573
|View full text |Cite
|
Sign up to set email alerts
|

Gendered STEM: A Systematic Review and Applied Analysis of Female Participation in STEM in the United Arab Emirates

Abstract: The present study aims to identify potential barriers that women in the United Arab Emirates might face if they pursue careers in science, technology, engineering, and mathematics (STEM). For this purpose, a systematic review and subsequent applied analysis of the UAE context was developed. The systematic review was reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and PRISMA Extension for Scoping Reviews. The review was performed on EBSCO, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Furthermore, some people believe that STEM fields are no longer considered male-only sectors in the UAE, as young girls are participating in schools and universities STEM courses actively, outperforming boys in several cases since the adaptation of STEM in schools (Zaatari, 2019), and Emirati women have continued to outnumber their male colleagues in STEM education, despite psychological, social and gender preconceptions, as well as cultural complications in having leadership roles (Pasha-Zaidi & Afari, 2016). Nonetheless, even though female participation in secondary and tertiary STEM education has increased with the UAE's economic development goals, the workforce continues to skew male (Alzaabi et al, 2021).…”
Section: Stem Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some people believe that STEM fields are no longer considered male-only sectors in the UAE, as young girls are participating in schools and universities STEM courses actively, outperforming boys in several cases since the adaptation of STEM in schools (Zaatari, 2019), and Emirati women have continued to outnumber their male colleagues in STEM education, despite psychological, social and gender preconceptions, as well as cultural complications in having leadership roles (Pasha-Zaidi & Afari, 2016). Nonetheless, even though female participation in secondary and tertiary STEM education has increased with the UAE's economic development goals, the workforce continues to skew male (Alzaabi et al, 2021).…”
Section: Stem Educationmentioning
confidence: 99%
“…Hence, Emirati women stressed on the importance of female mentors in affecting their career success, and they are constantly looking up to an appropriate female role model (Al Matroushi et al, 2020). Female mentors or role models are important for gender equity and closing the gender gap in male-dominated sectors, and Emirati women in STEM fields have a big desire to be role models for other females (Alzaabi et al, 2021).…”
Section: Role Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women in STEM fields, particularly engineering, face various challenges worldwide before, during, and after graduation. These challenges may include financial constraints, math anxiety, gender stereotypes, and the pursuit of career prestige, quality infrastructure, and amenities [20]. However, Arab women encounter additional obstacles that are predominantly rooted in social and cultural norms, including patriarchal cultures, gender stereotypes, and workplace discrimination, which lead to limiting their education and career growth and hindering their professional development.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic literature review identified potential barriers for women pursuing STEM careers, focusing on the UAE. The study concluded that job prospects remain limited despite increasing access for women in STEM [20]. Additionally, another systematic review of women's engagement experiences in STEM fields revealed that these experiences in engineering are influenced by personal characteristics such as self-efficacy, motivation, and passion, as well as the practices of male colleagues, parents, and human resources [21].…”
Section: Percentage Of Women Who Graduated In Stem Fields Among All G...mentioning
confidence: 99%